THE “AFTERLIFE” OF ICELAND BY DANIEL VETTER: CONTEMPORARY READINGS BY SONIA RAMMER AND PIOTR MILEWSKI - Rott, Dariusz (Prace Polonistyczne, 2021)
The article analyses the contemporary reception of the first Polish text describing Iceland, published in 1638 by a member of the Czech Brethren and the owner of a printing house in Leszno, Daniel Vetter (1592–ca. 1669). Islandia albo Krótkie opisanie wyspy Islandyji (Iceland, or a Short Description of the Island of Iceland), a result of Vetter’s journey to the island in his youth in 1613, was reprinted several times in the Czech Republic and Poland in the 19th and 20th centuries; it was also translated into Danish and Icelandic. Recently, it has inspired two interesting works: one by Sonia Rammer and the other by Piotr Milewski. Sonia Rammer creatively uses Daniel Vetter’s Iceland in her literary-graphic project entitled Kroniki islandzkie (The Icelandic Chronicles; with additional Supplement) created during her stay in Iceland as a resident. For her, Vetter’s report is a valuable source of artistic inspiration. In 2018, Piotr Milewski, the author of several documentary books, published Islandia albo najzimniejsze lato od pięćdziesięciu lat (Iceland or the Coldest Summer in 50 Years). He was also inspired by Vetter’s journey to Iceland. Four hundred years later, Milewski follows his footsteps, creatively rewriting the 17th-century report.